Functionalisation of the 1,3-bis(2-pyridylimino)isoindole (BPI) ligand via esterification - Sener, M. Kasim; Avciata, Ulvi (SAGE PUBLICATIONS LTD, 2007)
1,3-bis(2-pyridylimino)isoindolines (BPI) with N-donor groups and long alkyl chains were synthesised by DCC-activated esterification of mercaptoethanol-substituted bis(pyridylimino)isoindole with carboxylic acid derivatives (pyridine-4-carboxylic acid, nonanoic acid). Homoleptic iron(II) complex was synthesised by reaction of BPI with Fe(ClO4)(2) in acetone: chloroform. The new compounds were characterised by elemental analyses, FT-IR, H-1 NMR, C-13 NMR and UV-Vis spectral data.
Keywords: bis(pyridylimino)isoindole; N-donor ligands; iron complex; esterification; ISOINDOLINE COMPLEXES; RUTHENIUM COMPLEXES; OXIDATION; 1,3-BIS(2'-PYRIDYLIMINO)ISOINDOLINE; COORDINATION; OXYGENATION; MONONUCLEAR; PALLADIUM; RELEVANCE; BEHAVIOR; Chemistry